LOS RETOS QUE ENFRENTA EL DESARROLLO HUMANO INTEGRAL EN LA EDUCACIÓN SECUNDARIA LATINOAMERICANA (Memorias Sifored - Encuentros Educación UAN, 2023)
The different challenges that influence integral human development (IHD) are questioned and analyzed, from the difficulties faced by education in Latin America until today, to the lack of guarantees by governmental entities as well as teacher training. During the process, use is made of different research on the issues raised, used as theories and objects of study in different countries. The aim is to show the need for new public policies and the good use by teachers of pedagogy to counteract and support the educational process of individuals in different school contexts.
Keywords: Training for educational innovation; adolescence; education; human development